Rethinking history on the scriptures - Yaacob, Solehah@Nik Najah Fadilah (The Islamic Cultural Centre, London, 2018)
This paper focuses on some of the variations regarding the information in the scriptures-old testament or new testament-of the Bible. According to the Jews’ tradition, it is divided into five parts of their canonical books; Genesis, Exodus, Leviticus, Numbers and Deuteronomy. The so-called old testament is comprised of the Torah, which is also called ‘The Pentateuch’ or ‘the books of Prophets’. In addition, scholars have long recognised that even some of the books accepted into the canon are probably forgeries; the church has agreed that the Gospels of Mark, Mathew, Luke and John were authentic references for Christian principles. How about the other books within the Bible, are they authentic? Some believe that ‘Pseudonymous Writing’ occurred in these Gospels. In order to examine some communication barriers of non-canonical writings, this study concentrates on the reconciliation of the verses in the Bible and the Quran linguistically, historically and with respect to its authenticity.